Sixth Åland Island Conference on von Willebrand disease. (21st July 2022) - Berntorp, Erik; Trakymienė, Sonata S.; Federici, Augusto B.; Holstein, Katharina; Corrales‐Medina, Fernando F.; Pierce, Glenn F.; Srivastava, Alok; Prondzinski, Mario von Depka; Johnsen, Jill M.; Zupan, Irena P.; Halimeh, Susan; Nummi, Vuokko; et al.
Abstract: Introduction: The sixth Åland Islands Conference on von Willebrand disease (VWD) on the Åland Islands, Finland, was held from 20 to 22 September 2018. Aim: The meeting brought together experts in the field of VWD from around the world to share the latest advances and knowledge in VWD. Results and discussion: The topics covered both clinical aspects of disease management, and biochemical and laboratory insights into the disease. The clinical topics discussed included epidemiology, diagnosis and treatment of VWD in different countries, management of children with VWD, bleeding control during surgery, specific considerations for the management of type 3 VWD and bleeding control in women with VWD. Current approaches to the management of acquired von Willebrand syndrome were also discussed. Despite significant advances in the understanding and therapeutic options for VWD, there remain many challenges to be overcome in order to optimise patient care. In comparison with haemophilia A, there are very few registries of VWD patients, which would be a valuable source of data on the condition and its management. VWD is still underdiagnosed, and many patients suffer recurrent or severe bleeding that could be prevented. Awareness of VWD among healthcare practitioners, including non‐haematologists, should be improved to allow timely diagnosis and intervention. Diagnosis remains challenging, and the development of fast, simple assays may help to facilitate accurate and rapid diagnosis of VWD.